2019
DOI: 10.1016/j.scitotenv.2019.01.365
|View full text |Cite
|
Sign up to set email alerts
|

The disappearing Salton Sea: A critical reflection on the emerging environmental threat of disappearing saline lakes and potential impacts on children's health

Abstract: Changing weather patterns, droughts and competing water demands are dramatically altering the landscape and creating conditions conducive to the production of wind-blown dust and dust storms. In California, such factors are leading to the rapid shrinking of the Salton Sea, a 345 square mile landlocked "sea" situated near the southeastern rural border region known as the Imperial Valley. The region is anticipated to experience a dramatic increase in wind-blown dust and existing studies suggest a significant imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Rural communities in the southwestern USA and along the USA–Mexico border face changing weather patterns, droughts, and competing water demands that are dramatically altering the landscape and creating conditions conducive to the production of wind-blown dust. As the Salton Sea recedes, primarily due to local changes in water supplies and reductions in agricultural runoff, it is anticipated that 40–80 more tons of dust per day will be released into the local environment [45], exposing large swaths of playa and generating wind-blown dust [13]. Because the particulates from dried lakebeds have been shown to be smaller in size, they are more easily respirable by humans [46], and such substantial increases in dust have the potential to significantly impact the respiratory health and quality of life for nearby residents [9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural communities in the southwestern USA and along the USA–Mexico border face changing weather patterns, droughts, and competing water demands that are dramatically altering the landscape and creating conditions conducive to the production of wind-blown dust. As the Salton Sea recedes, primarily due to local changes in water supplies and reductions in agricultural runoff, it is anticipated that 40–80 more tons of dust per day will be released into the local environment [45], exposing large swaths of playa and generating wind-blown dust [13]. Because the particulates from dried lakebeds have been shown to be smaller in size, they are more easily respirable by humans [46], and such substantial increases in dust have the potential to significantly impact the respiratory health and quality of life for nearby residents [9,10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may help provide a better understanding of the health needs of the community, as well as strategies to inform community-specific preventive programs to address the symptoms of asthma and respiratory impairment. The disappearance of the Salton Sea will likely have unforeseen public health implications, while children and people with preexisting health conditions, such as asthma, may be more vulnerable to the impacts of such environmental changes [13,47,48]. Future research will longitudinally examine children’s respiratory health, incorporating both ambient exposure measurements and physiological assessments over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health‐related consequences of the California drought in this region have gained attention in recent years (Johnston et al, 2019); however, the specific environmental changes related to drought and their effects on human health remain largely understudied. Future research in this area may be guided by comparing the Salton Sea with similar, highly studied regions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the filters were dominated by large crustal particles up to 30 µm in diameter that matched local soils, and that windblown dust was a major source on high PM days. Windblown dust in the area has also been extensively investigated with respect to the increasing importance of dust emissions from exposed beds of the Salton Sea, which bounds the valley to the north [13][14][15][16][17][18]. Windblown dust events also lead to PM10 regulatory exceedances in the air basin [19].…”
Section: Introductionmentioning
confidence: 99%